IT PROFESSIONAL COMPETENCES AND THE REQUIREMENTS OF THE LABOUR MARKET: EXPERIENCE OF THE UNITED KINGDOM - Gray, E. (Journal of Information Technologies in Education (ITE), 2009)
Understanding the employment market while defining specific skill sets associated with potential graduates is always important for courses in higher education.